Analisis Strategi Promosi Gadai Emas Di PT Bank Aceh Syariah Cabang Kuala Simpang - Irwanto; Ningsih, Juwita Adelia (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2023)
This final project is entitled “Analysis of Gold pawn promotion Strategy at Pt Bank Aceh Syariah Cabang Kuala Simpang”. This type of research used a qualitative descriptive approach, namely describing and analyzing the problems found. Qualitative research is based on primary and secondary data. Primary data was obtained thourgh interviews and documentation, while secondary data was obtained through related books. With research The purpose oh this research is to analyze the types of gold pawing promotion strategies and to evaluate the application of gold pawingstrategies related to advertising personal selling, sales promotion, and public relation at Pt Bank Aceh Syariah Cabang Kuala Simpang Branch. What are the obstacles in implementing this strategy. The result of this study indicate that the strategy is good enough, but there are still obstacles, namely the lack of human resources in the gold pawing section, theref ore promotion in the public relations and direct sales section cannot be carried out. Increase in customers and revenue in every year.